Public thoughts on incentivizing COVID-19 vaccine uptake in the United States: testing hostile media bias with user-generated comments - Gearhart, Sherice; Coman, Ioana A.; Moe, Alexander; Brammer, Sydney E. (Frontiers in Sociology, 2023)
Facebook is the most popular social media platform and often used by news organizations to distribute content to broad audiences. Features of this online news environment, especially user-generated comments shown to news consumers, have the potential to induce audience perceptions of hostile media bias. This study furthers investigation into the influence of exposure to Facebook comments and news topics on consumers. Using a sample of U.S. adult Facebook users (N = 1,274), this work utilized a 2 (likeminded comments or disagreeable comments) × 2 (story topic of requiring COVID-19 vaccines to receive a monetary bonus or maintain employment) between-subjects experimental design. While controlling for the influence of partisanship, this work further proves that features of the Facebook environment uniquely influence news audience perceptions of neutral news content. Specifically, findings indicate that news story topic can influence perceptions of bias. Further, topic and comment exposure interacted, demonstrating the intensity of story topic and likeminded comments enhance hostile media perceptions.